Quantitative analysis method and application of high-throughput in-situ titration of active intermediates based on electrochemically gated semiconductors

CN121721206BActive Publication Date: 2026-10-09UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610067566.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-19
Publication Date
2026-10-09
Estimated Expiration
2046-01-19

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种电化学栅控高通量SI-SECM方法,通过构筑金属-半导体肖特基结构(Pt-TiO2),并施加负偏压实现基底导电性的可逆调控,从而解决传统SI-SECM在宏观导电大基底上易出现的自发正反馈问题,实现高空间分辨率与高通量的瞬态电化学测试

Benefits of technology

本发明提出并验证了一种基于金属-半导体肖特基势垒的电化学栅控策略,构筑了Pt-TiO2-FTO阵列结构的高通量SI-SECM测量平台。与现有的SI-SECM技术需严格保证尖端与基底尺寸匹配不同,本发明通过在TiO2半导体上引入可调Pt阵列,利用Pt与TiO2之间自然形成的肖特基势垒,实现了对基底导电性的外加电位调控,从根本上抑制了传统SI-SECM在大面积导电基底上易产生的自发正反馈信号。本发明的技术方案有利于解决传统SI-SECM在宏观导电大基底上难以进行高通量瞬态测量的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121721206B_ABST
    Figure CN121721206B_ABST
Patent Text Reader

Abstract

The application discloses an electrochemical gate-controlled high-flux in-situ titration method based on a metal-semiconductor Schottky barrier and application of the method in analysis of electrocatalytic active intermediates. By constructing a Pt array on TiO2 and applying an external potential to regulate the Schottky barrier, the conductivity of the substrate is reversibly switched, spontaneous positive feedback current generated by traditional SI-SECM on a conductive large substrate is effectively inhibited, and high-flux, high-resolution quantitative detection of active intermediates is realized. Experimental and theoretical researches show that the size of Pt nanoparticles and the potential of the substrate jointly regulate the coverage and kinetic behavior of H, wherein the small-size Pt cluster has an up-shifted d-band center, stronger interface charge rearrangement and lower hydrogen generation energy barrier, thereby exhibiting faster H kinetics. UPS, Mott-Schottky, EIS and DFT calculation confirm that the Pt-TiO2 interface forms an adjustable Schottky barrier and enhances charge transmission. The method provides an efficient and reliable analysis platform for the study of structure-activity relationship in electrocatalytic reactions, and has wide application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemistry, specifically to a quantitative analysis method for high-throughput in-situ titration of active intermediates in electrochemical gated semiconductors, and the application of this method in hydrogen evolution reaction kinetic testing and electrocatalytic mechanism research. Background Technology

[0002] The overuse of fossil fuels has led to environmental problems such as energy depletion and greenhouse gas emissions, exacerbating the global energy crisis and climate change. Developing clean, efficient, and sustainable energy conversion and storage technologies has therefore become a research focus. Among these, electrocatalytic hydrogen evolution reaction (HER) and carbon dioxide reduction reaction (CO2RR) are of great significance for hydrogen energy development and carbon recycling. A deep understanding of electrocatalytic mechanisms requires in-situ quantitative characterization of key information on the electrode surface, especially active sites and reaction intermediates. This is crucial for revealing structure-performance relationships and optimizing catalyst design. Existing characterization techniques, such as transmission electron microscopy (TEM), X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Raman spectroscopy, infrared (IR) spectroscopy, mass spectrometry, and inductively coupled plasma mass spectrometry (ICP-MS), while providing important information for catalyst structure analysis, have limitations in sensitivity, spatiotemporal resolution, and the ability to capture transient intermediates. Other methods, such as those for CO and NO2... ⁻ Probe methods, however, are limited by testing environments or selectivity, making them difficult to apply universally. In contrast, scanning electrochemical microscopy (SECM), a scanning probe technique based on ultra-microelectrodes to detect redox processes in solution, can measure local currents or potentials at nanometer-level resolution. It offers advantages such as in-situ, quantitative analysis, and high spatial resolution, providing a unique tool for studying electrode interface reaction mechanisms. Building on this, Bard et al. first proposed surface titration scanning electrochemical microscopy (SI-SECM) in 2008 for the quantitative determination of adsorbed species coverage and kinetic constants on electrode surfaces, and it has now been applied to detect various intermediates such as adsorbed hydrogen and hydroxyl radicals. However, traditional SI-SECM still faces technical bottlenecks: on large-area conductive substrates, the tip's proximity can easily trigger spontaneous positive feedback currents due to concentration polarization, severely interfering with the resolution of transient titration signals. To avoid this problem, experiments must strictly ensure the size matching between the tip and the substrate, which not only increases operational complexity but also greatly limits its application potential in rapid, large-area screening. Therefore, constructing a platform that can maintain the stability of the interface electronic structure and is suitable for high-throughput transient electrochemical measurements remains a significant challenge in current electrochemical interface research. Summary of the Invention

[0003] The purpose of this invention is to provide an electrochemically controlled high-throughput SI-SECM method. This method achieves reversible control of substrate conductivity by constructing a metal-semiconductor Schottky structure (Pt-TiO2) and applying a negative bias voltage. This solves the problem of spontaneous positive feedback that easily occurs in traditional SI-SECM on macroscopically conductive large substrates, enabling high spatial resolution and high-throughput transient electrochemical testing. To address this technical problem, this invention provides the following technical solution: 1. A method for preparing a pointed carbon electrode, comprising the following steps: S1 involves stretching a borosilicate glass tube in a commercially available CO2 laser stretching instrument to obtain a capillary. S2 uses conductive silver paste to connect and fix the carbon rod to the nickel-chromium metal wire and inserts it into the stretched glass tube, ensuring that the front end of the carbon rod is properly exposed. S3 uses the negative pressure of a vacuum pump to inject epoxy resin into the tube body, so that it fully fills the metal connection parts. After S4 is placed vertically and allowed to cure at room temperature with epoxy resin, its RG value is ground to a fixed value (RG = electrode radius plus glass sleeve / electrode radius). Before each use, the S5 tip electrode is polished with alumina paste on a microfiber pad and then cleaned with deionized water. 2. A pretreatment method for fluorine-doped single-sided conductive glass (FTO) includes the following steps: S6 uses FTO as a substrate and is first ultrasonically cleaned in anhydrous ethanol for 20 minutes. S7 is rinsed with acetone 1-2 times in a fume hood to remove surface organic impurities, and then thoroughly rinsed with deionized water to remove any remaining acetone. S8 immerses FTO in ethanol and sonicates it for 20 minutes, then places it in a vacuum drying oven to dry for later use; 3. The preparation method of the TiO2-FTO layer includes the following steps: S9 was mixed with nano-TiO2 powder and water-soluble resin at a mass ratio of 7:3, and anhydrous ethanol was added and ultrasonically dispersed for 10 minutes to obtain a uniform TiO2 dispersion. S10 uses a commercially available spray gun to draw up TiO2 dispersion and sprays it evenly onto the FTO conductive surface; S11 The FTO coated with TiO2 was placed in a muffle furnace for annealing for 1 hour to enhance the film adhesion and obtain a stable TiO2-FTO layer. 4. A method for fabricating a Pt-TiO2-FTO high-throughput array substrate, comprising the following steps: S12 places the metal mask tightly against the TiO2-FTO surface and seals the remaining area with tape; S13 uses a plasma magnetron sputtering system to sputter Pt onto the TiO2-FTO surface under a fixed vacuum and current. S14 uses a progressive masking method in the row direction for gradient sputtering, so that different positions can obtain different cumulative sputtering times; S15 repeats the shielding sputtering process in the column direction to form a two-dimensional Pt content gradient, thus obtaining a Pt-TiO2-FTO high-throughput array substrate containing multiple Pt loadings. 5. The quantitative analysis method for high-throughput SI-SECM in-situ titration of *H includes the following steps: S16 places the carbon electrode and the prepared Pt-TiO2-FTO high-throughput array substrate in an electrolyte containing FcMeOH, and adjusts the distance between the tip and the Pt array points according to the approximation curve so that the tip is in a position that can achieve full collection efficiency. S17 applies a negative bias voltage to the Pt-TiO2-FTO array substrate for a certain period of time, causing the TiO2 semiconductor energy band to bend downwards. Electrons cross the metal-semiconductor interface barrier and are injected into the Pt surface, driving water molecules to be reduced to generate *H. S18 removes the negative bias voltage, causing the Pt-TiO2 interface to reform the Schottky barrier, thus restoring the substrate from a conductive state to an insulating state. After removing the negative bias voltage from S19, a potential for oxidizing FcMeOH is quickly applied to the tip, causing FcMeOH to... + It is generated at the tip and undergoes an electrochemical reaction with the *H on the surface of the array point to obtain a transient titration current signal; The S20 collects the titration current-time curve, subtracts the background current under the open-circuit condition of the substrate, and calculates the corresponding titration charge by integration, and then calculates the surface adsorbed hydrogen coverage. S21 sets different delay times t between substrate generation and tip collection. delay Repeat steps S16-S20, and record ln[*H] as t delay The variation law of *H was used to fit the dynamic rate constant of *H. S22 repeats steps S16-S21 for multiple Pt sites in the Pt-TiO2-FTO array to obtain the *H coverage and kinetic rate constant of different array sites, thereby achieving parallel quantitative analysis of multiple catalytic sites. Preferably, the original dimensions of the glass tube in step S1 are an outer diameter of 1 mm, an inner diameter of 0.2 mm, and a length of 10 cm. Preferably, the carbon rod in step S2 is about 1 cm long and 270 micrometers in diameter. Preferably, the electrode RG in step S4 is about 2.3. Preferably, the FTO size in step S6 is 1.0 cm × 3.0 cm × 0.2 cm. Preferably, the vacuum drying temperature in step S8 is 80°C and the drying time is 30 minutes. Preferably, in step S9, the TiO2 dispersion consists of 70.0 mg TiO2 powder (P25), 30 mg water-soluble resin, and 5 mL anhydrous ethanol. Preferably, the nozzle diameter of the spray gun used in step S10 is 0.3 mm, the volume of TiO2 dispersion liquid drawn is 200 μL, and the spraying area is preferably 1.0 cm × 1.0 cm. Preferably, the muffle furnace annealing temperature in step S11 is 400°C. Preferably, in step S12, the metal mask has a 9×9 aperture structure with a aperture diameter of approximately 200 micrometers. Preferably, in step S13, the vacuum level of the sputtering cavity is 4.0 Pa (argon atmosphere), and the sputtering current is 11 mA. Preferably, the time gradient in steps S14 and S15 is 0.5 minutes. Preferably, in step S16, the electrolyte for FcMeOH consists of 0.1M KCl, 1mM FcMeOH, and 10mM KOH, and the distance between the tip and the Pt array points is 2-3 micrometers. Preferably, in step S17, a 0V (vs. RHE) voltage is applied to the Pt-TiO2-FTO array substrate for 500 milliseconds. Preferably, in step S19, the potential of the tip used to oxidize FcMeOH is 1.3V (vs. RHE). Preferably, in step S20, the titration current-time curve is collected for 50 seconds. Preferably, the delay time between substrate generation and tip collection in step S21 is set to 1 millisecond, 200 milliseconds, 500 milliseconds, 1000 milliseconds, or 2000 milliseconds. This solution provides an electrochemically controlled high-throughput SI-SECM quantitative analysis method and its application, which is achieved through the above method. Compared with the prior art, the present invention has the following advantages: This invention proposes and verifies an electrochemical gate control strategy based on a metal-semiconductor Schottky barrier, constructing a high-throughput SI-SECM measurement platform with a Pt-TiO2-FTO array structure. Unlike existing SI-SECM technologies that require strict matching of tip and substrate dimensions, this invention introduces a tunable Pt array onto a TiO2 semiconductor, utilizing the naturally formed Schottky barrier between Pt and TiO2 to achieve external potential modulation of substrate conductivity. This fundamentally suppresses the spontaneous positive feedback signal easily generated by traditional SI-SECM on large-area conductive substrates. The technical solution of this invention helps to solve the problem of difficulty in performing high-throughput transient measurements on macroscopically conductive large substrates using traditional SI-SECM. The electrochemical gate control principle proposed in this scheme has been verified through systematic experiments, demonstrating significant feasibility and reliability. First, in-situ electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and Mott-Schottky tests clearly demonstrate that the Pt-TiO2 interface exhibits tunable charge transport capability under applied bias, enabling reversible switching between "insulating" and "conductive" states. UPS testing further precisely determined the work function and valence band top position of Pt and TiO2, confirming that their electronic structure can form a tunable Schottky barrier. Second, in high-throughput SI-SECM experiments, the prepared Pt array achieved stable readout of 81 independent electrocatalytic sites, obtaining size-dependent *H generation rate, kinetic constants, and transient current response characteristics, which are completely consistent with theoretical calculations of the d-band center position, interfacial charge rearrangement strength, and reaction barrier changes. Attached Figure Description The accompanying drawings, which are included to provide a further understanding of embodiments of the invention and form part of this application, do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the principle of electrochemical gate-controlled high-throughput SI-SECM based on the metal-semiconductor Schottky barrier. Figure 2 The image shows the XRD pattern of Pt-TiO2-FTO. Figure 3 The following are partial EDS element distribution diagrams of a Pt-TiO2 high-throughput array: (a) shows the element distribution of the high-throughput Pt array, with Pt elements in the green area, O elements in the purple area, and Ti elements in the yellow area; (b) shows the distribution of Pt elements; (c) shows the distribution of Ti elements; and (d) shows the distribution of O elements. Figure 4 The images are SEM images of a Pt-TiO2 high-throughput array. (a) SEM image of a partial area of ​​the 9×9 Pt array, with the red-marked areas being the subsequent high-throughput SI-SECM test points; (bf) SEM images of points 1-5. Figure 5 The selected 5 points are the EDS energy spectra, and the energy spectra of the elemental contents of points 1-5 are (ae). Figure 6 Pt nanoparticle size distribution on the surface of points 1-5; (a) Pt nanoparticle size variation diagram on the surface of points 1-5; (bf) Statistical diagram of Pt nanoparticle size distribution on the surface of points 1-5. Figure 7 The UPS spectra of Pt-TiO2 and TiO2 are shown in (a) UPS spectrum of Pt-TiO2 and (b) UPS spectrum of TiO2. Figure 8 The Mott-Schottky curves of Pt-TiO2 and TiO2 in 0.1M KCl and 10mM KOH electrolytes at a frequency of 500Hz are shown. Figure 9 The EIS curves of bare TiO2 in 0.1 M KCl and 10 mM KOH electrolytes at different potentials (vs. OCP) are shown. (a) EIS curve of TiO2 from -0.1 V to -0.7 V; (b) EIS curve of TiO2 electrode from -0.4 V to -0.7 V and the equivalent circuit model used for fitting. Figure 10 The CV curves of bare TiO2 before and after applying a negative bias (-0.7 to -1.2 V, 10 s) in electrolytes of 1 mM FcMeOH, 0.1 M KCl and 10 mM KOH. Figure 11 The tip CV curves and approximation curves used in the SI-SECM experiment are shown. (a) Tip CV curve (scan rate of 0.005 mV s). -1 (b) Normalized approximation curves obtained by theoretical approximation in electrolytes of 1 mM FcMeOH, 0.1 M KCl and 10 mM KOH. I T L and L represent the normalized tip currents ( I T = i T / i T,∞ ) and the normalized tip-to-base distance (L = d / a, where a is the tip radius). Figure 12Electrochemical titration of surface *H on a single Pt array (sputtering time of 1 minute) is shown in (a) titration curves acquired at different substrate potentials (vs. RHE); and (b) delayed titration curves at 0 V (vs. RHE) with delay times ranging from 1 to 2000 ms. The inset shows the kinetic rate constant of surface *H obtained by fitting the *H coverage as a function of delay time. Figure 13 For high-throughput electrochemical titration of Pt array surface *H, (a) titration curves were collected on TiO2 surface at different substrate potentials (vs. RHE); (bf) titration curves were collected on surfaces 1-5 at different substrate potentials. Figure 14 The graph shows the relationship between the charge collected on TiO2 and the surface at points 1-5 and the potential. Figure 15 For the delayed-time titration of surface *H of a high-throughput Pt array, (ae) at 0 V (vs. RHE), the delayed titration curves of surface *H at points 1-5 are shown. Figure 16 Let be the kinetic rate constant of surface *H of the high-throughput Pt array, and (ae) be the kinetic rate constant of surface *H at point 1-5. Figure 17 The graph shows the variation of the kinetic rate constant for point 1-5*H. Figure 18 The optimized structural model used in theoretical calculations, (ad)Pt6-TiO2, Pt 13 -TiO2, Pt 19 -TiO2, Pt(111) structural model. Figure 19 To theoretically calculate the size-dependent *H behavior of Pt, (a) Pt clusters of different sizes (Pt6-TiO2, Pt 13 -TiO2, Pt 19 Partial density of states (PDOS) of Pt d orbitals and adsorbed H 1s orbitals in Pt (111) and Pt (-TiO2), with insets showing Pt6 and Pt 13 and Pt 19 (a) Differential charge density distribution on TiO2, with blue areas representing electron accumulation and yellow areas representing electron depletion, with an equivalent value of 0.005 electrons / ų; (b) Free energy curves for the hydrogen evolution reaction on different models; (c) Correlation between the Ptd band center and the RDS free energy barrier.

[0004] Example 1 Cutting-edge fabrication: Based on the manufacturing technology of disk-shaped metal nanoelectrodes (or nano-tip) using a commercially available CO2 laser drawing instrument, a carbon rod with a diameter of 270 μm is fabricated into a microelectrode with an RG (RG = electrode radius plus glass sleeve / electrode radius) of approximately 2.3 using an epoxy resin encapsulation method. The epoxy resin encapsulation process mainly includes three steps: "stretching", "assembly", and "sealing". First, a 10 cm long borosilicate glass tube (outer diameter 1 mm / inner diameter 0.2 mm) is stretched into a capillary tube in a commercially available CO2 laser drawing instrument for later use. Then, a ~1 cm carbon rod is connected and fixed to a nickel-chromium metal wire using conductive silver paste and inserted into the stretched glass tube, ensuring that the front end of the carbon rod is appropriately exposed. Next, epoxy resin is injected into the tube body using a vacuum pump under negative pressure to fully fill the metal connection area. Finally, after the epoxy resin is allowed to cure vertically at room temperature, its RG is polished to approximately 2.3. Before each use, it is polished with alumina paste on a microfiber pad and cleaned with deionized water. Substrate fabrication: This invention uses fluorine-doped single-sided conductive glass (1.0 cm × 3.0 cm × 0.2 cm) as the substrate. Before use, strict surface pretreatment is performed in sequence: first, ultrasonic cleaning in anhydrous ethanol for 20 min to remove organic impurities on the surface, then rinsing with acetone 1-2 times in a fume hood, and thoroughly cleaning the residual acetone with deionized water, then ultrasonic cleaning in anhydrous ethanol for 20 min again, and finally drying in a drying oven at 70-80 ℃ for later use. The TiO2 layer was prepared by spraying. Anhydrous ethanol was added and ultrasonically dispersed according to a ratio of 70 wt% nano-TiO2 and 30 wt% water-soluble resin to obtain a uniform slurry. This slurry was then uniformly sprayed onto the conductive surface of FTO using a commercially available spray gun (nozzle diameter 0.3 mm), with an area controlled at 1.0 cm × 1.0 cm. Annealing was then performed at 400 °C for 1 h to enhance film adhesion. The Pt array was deposited using plasma magnetron sputtering. First, a metal mask (1.0 cm × 1.0 cm with a 9 × 9 array of openings, approximately 200 μm in diameter) was tightly attached to the TiO2 surface, and the remaining area was sealed with tape. Sputtering was then performed under a vacuum of 4.0 Pa (Ar in the sputtering chamber) and a sputtering current of 11 mA, with a single 1-minute sputtering cycle yielding a single Pt array. Furthermore, to achieve high-throughput control, an orthogonal sputtering strategy with a time step of 0.5 min was adopted. That is, rows 2-9 were gradually masked in the row direction, so that the first row was exposed in all 9 sputterings and obtained a cumulative deposition time of 4.5 min, the second row obtained 4.0 min, and so on until the ninth row was exposed only once and obtained a deposition time of 0.5 min. Then, gradient sputtering was continued in the column direction with the same masking method for 0.5 min, forming a superposition effect, so that each array point has an independent and different cumulative sputtering time, and finally a Pt-TiO2-FTO high-throughput array containing 81 points with different Pt contents was obtained.

[0005] Example 2 SI-SECM experiments were performed using a Mintech super-resolution electrochemical microscope (MT-SRECM200). The prepared substrate was mounted in a dedicated high-throughput electrolytic cell for the SI-SECM, which was made of polytetrafluoroethylene and integrated with reference and counter electrode interfaces to achieve a unified four-electrode system. The electrolytic cell was fixed on the SECM three-dimensional positioning platform, with Ag / AgCl as the reference electrode, platinum wire as the counter electrode, the prepared carbon microelectrode as the tip, and Pt-TiO2-FTO as the substrate. Subsequently, an electrolyte solution of 0.1M KCl, 1mM FcMeOH, and 10mM KOH was injected into the electrolytic cell until the four-electrode system was completely immersed. Before the experiment, dissolved oxygen in the solution was removed by purging with argon gas for 15-20 min. Next, the tip was coarsely adjusted above a specific Pt array point using a piezoelectric controller. A voltage of 1.3V (vs. RHE) was applied to the tip to oxidize FcMeOH to FcMeOH⁺, while a voltage of 0V (vs. RHE) was applied to the substrate. Precise positioning in three-dimensional space ensured that the distance between the tip and the Pt array points on the substrate reached approximately 2-3µm, at which point the tip's collection efficiency reached its theoretical maximum (100%). Finally, a voltage was applied to the substrate for 500ms to generate *H, and data was collected for 50s using chronoamperometry (CA) in SI-SECM mode. The test potential in the experiment can be converted to a reversible hydrogen electrode (RHE) according to the following calibration equation: Set different delay times (t) between *H generation and titration. delay By integrating the delayed titration curve and subtracting the background current, the surface active hydrogen coverage can be calculated using the following formula: Q is the integrated charge, F is the Faraday constant (96485 C / mol), n is the number of electrons transferred (n = 1 in this experiment), and R is the radius of the Pt array points (100 μm). This calculation is based on the geometric area of ​​the Pt array points and assumes that their surface activity is uniformly distributed. Figure 1 A schematic diagram illustrating the structure and principle of Example 1 is shown. Specifically, if a high-throughput SI-SECM experiment is performed directly using a large-area conductive substrate, the tip near the substrate surface will induce a spontaneous positive feedback current due to concentration polarization, thus masking the true titration signal. At the metal-semiconductor interface, if the work function of the semiconductor is less than that of the metal (e.g., n-type TiO2 and Pt), electrons will spontaneously migrate from the semiconductor to the metal until their Fermi levels converge. Therefore, at open-circuit potential, a Schottky barrier forms at the TiO2-Pt contact, and the substrate as a whole exhibits insulating properties, preventing spontaneous positive feedback. When a negative bias is applied, the energy band of TiO2 bends downward, allowing electrons to cross the barrier and inject into the Pt surface, further entering the LUMO orbitals of water molecules in the electrolyte, driving water reduction to generate *H. After the bias is removed, the Schottky barrier at the Pt / TiO2 interface recovers, the energy band flattens out, and only the reaction signal between *H and FcMeOH⁺ is retained. Figure 2 The XRD pattern of Pt-TiO2-FTO prepared in Example 1 is shown. The XRD pattern clearly shows the diffraction peaks of the anatase phase TiO2 (PDF#21-1272) and the characteristic peaks of Pt (PDF#04-0802), and no other impurity peaks were observed, indicating that the prepared substrate has high purity and crystallinity, proving the successful loading of Pt on the TiO2 substrate. EDS surface distribution results ( Figure 3 The images show that Ti and O elements are uniformly distributed on the substrate, while the Pt element signal gradually increases with the array position, verifying the effectiveness of the orthogonal sputtering strategy in constructing arrays with different Pt contents. (SEM images) Figure 4 The results showed that the size of the Pt nanoparticles on the array sites gradually increased with the adjustment of experimental conditions. Statistical particle size analysis further confirmed that the size increased from approximately 35 nm to approximately 78 nm. Figure 6 The Pt content of its surface load is also gradually increasing. Figure 5 This indicates that magnetron sputtering conditions have a significant regulatory effect on particle growth. To verify the existence of a Schottky barrier between Pt and TiO2, UPS tests were performed on Pt-TiO2 and TiO2 respectively. The results showed that the work function of TiO2 was approximately 3.75 eV, while that of Pt was approximately 4.52 eV. Figure 7The results show that the introduction of Pt significantly enhances the work function and shifts the valence band maximum (VBM) to a lower binding energy, modulating the interfacial electronic structure and directly proving the formation of a tunable Schottky barrier at the Pt-TiO2 interface. Furthermore, Mott-Schottky tests further confirm this behavior. Figure 8 The flat-band potential of Pt-TiO2 (0.29 V vs. RHE) showed a negative change compared to bare TiO2 (0.38 V vs. RHE), indicating significant band bending at the interface. Furthermore, the carrier concentration increased from 6.79 × 10⁻⁶. 19 cm -3 (TiO2) increased to 1.85 × 10 20 cm -3 (Pt-TiO2) shows an increased electron density and a lower barrier height due to Pt loading, consistent with the formation of a tunable Schottky junction. This Schottky barrier suppresses the reverse transfer of electrons from Pt back to TiO2, making the substrate non-conductive under open-circuit conditions and preventing spontaneous positive feedback common in large conductive substrates. EIS measurements show a significant decrease in resistance when a negative bias is applied. Figure 9 This confirms that the conductivity of TiO2 increases under negative bias. When the negative bias is removed, the substrate rapidly recovers its insulating behavior, as evidenced by the overlapping CV curves of bare TiO2 before and after the application of negative bias. Figure 10 This has been verified. Figure 11 The tip CV curve and approximation curve used in Example 2 are shown. To verify the feasibility of this high-throughput SI-SECM system, an electrochemical titration experiment was conducted using a Pt array with a sputtering time of 1 min as a model. Baseline current was collected under open-circuit conditions, and electrochemical titration signals at different potentials (+0.2 V to –0.3 V vs. RHE) were obtained using a stepped potential scan method (100 mV increments). Figure 11 (a) The results show that as the potential shifts negatively, the area of ​​the integral curve gradually increases, corresponding to an increase in the amount of charge, indicating that it can interact with FcMeOH. + The amount of *H in the reaction was significantly increased. Next, different delay times ranging from 1 to 2000 ms were set at 0V (vs. RHE). The results showed that with t delay The titration curve gradually decays over time, indicating that the amount of *H available for titration of FcMeOH⁺ decreases with time. Figure 12 (b). Furthermore, different t delay A linear fit was performed on ln[*H], and the absolute value of the slope is the kinetic rate constant of *H under that condition, which is 0.58 s. -1 ( Figure 12(See inset b). Therefore, even on a large-area conductive substrate, the Pt-TiO2-FTO semiconductor gate control system used in this invention can still maintain its insulation characteristics in the open-circuit state, effectively suppressing spontaneous positive feedback current and ensuring the authenticity and resolvability of the titration signal. Furthermore, based on the same method, using a high-throughput Pt array as a model, electrochemical titration was performed on five Pt array points in the red-marked region. Figure 13 The results show that (). Figure 14 The negative potential shift and extended sputtering time significantly increased the integral area and charge of the titration curve, indicating a corresponding increase in the amount of surface *H. Comparing the signal collected from the TiO2 substrate, it was found that the signal intensity on the Pt surface was much greater than that on the TiO2 surface, confirming that the signal indeed originated from *H adsorbed on the Pt surface. Next, delayed titration experiments were conducted at 0 V (vs. RHE) with different t values. delay The titration curves under the given conditions all showed a decreasing trend with increasing time. Figure 15 Integrating the curve and fitting a linear relationship ( ). Figure 16 After obtaining the rate constants at different sputtering times, Figure 17 The results showed that the rate constant gradually decreased with increasing sputtering time, indicating that the kinetic behavior of *H was somewhat suppressed as the particle size increased. Combined with the SEM characterization results, this trend can be attributed to the change in the size of Pt nanoparticles. Pt nanoparticles formed at shorter sputtering times are smaller, have a higher specific surface area and more abundant unsaturated surface atomic sites, which are conducive to the rapid generation and transformation of *H, thus exhibiting a higher kinetic rate constant. However, as the sputtering time increases, the particles gradually grow larger and tend to aggregate, leading to a decrease in specific surface area and a reduction in low-coordination active sites on the surface, thereby limiting the generation and reaction rate of *H. To illustrate the effect of particle size on hydrogen adsorption kinetics, an optimized structural model was used ( Figure 18 Density functional theory calculations were performed. The results show that the density of states characteristics of Pt nanoclusters of different sizes loaded on TiO2 vary significantly with size. Figure 19 (a) The smaller Pt d band center shifts upward, closer to the Fermi level, thus enhancing the coupling between the Pt d orbitals and the H 1s orbitals, facilitating electron injection and promoting the generation of adsorbed hydrogen. Interfacial charge density difference distribution ( Figure 19 The inset (a) further shows that there are significant differences in the degree of electron rearrangement of Pt clusters of different sizes on the TiO2 surface: Pt6-TiO2 exhibits the most significant electron depletion and enrichment at the interface, indicating that smaller Pt clusters have a stronger interfacial electron exchange capacity. A comparison of the changes in water reduction free energy of Pt clusters of different sizes is also shown. Figure 19(b) The results show that Pt6-TiO2 exhibits a near-thermally neutral free energy change in the key intermediate (*H + *OH) stage, and its activation energy for the rate-determining step is also lower than that of larger Pt clusters, indicating that smaller Pt clusters are more favorable for hydrogen adsorption and conversion. This is further supported by the relationship between the Pt d-band center position and the energy barrier of the rate-determining step ( Figure 19 As can be further seen in c), as the Pt size decreases, the d-band center shifts upward toward the Fermi level, accompanied by a decrease in the free energy barrier. This trend indicates that small-sized Pt clusters exhibit higher reactivity in hydrogen adsorption due to their more favorable electronic structure and interfacial charge regulation characteristics. In summary, this invention proposes an innovative analytical strategy that overcomes the feedback limitations of traditional SI-SECM on large conductive substrates by constructing an electrochemical gated system based on a metal-semiconductor Schottky barrier. By constructing a Pt array on a TiO2 substrate, controllable adjustment of the substrate conductivity is achieved, enabling high-throughput in-situ titration and *H kinetics determination at multiple catalytic sites. Experimental results show that *H coverage and kinetic rate constants are jointly regulated by the substrate potential and the size of the Pt nanoparticles, with smaller Pt clusters exhibiting faster hydrogen kinetics. Further theoretical calculations using UPS, Mott-Schottky, EIS, and DFT comprehensively reveal the regulatory effects of Pt loading on the TiO2 work function, band structure, and interfacial Schottky barrier, and elucidate the decisive influence of Pt size on the d-band center position, interfacial electron exchange intensity, and *H adsorption energy. The study found that smaller Pt clusters possess an upwardly shifted d-band center, stronger interfacial charge rearrangement, and more efficient hydrogen adsorption and activation capabilities, thereby significantly reducing the free energy and activation barrier of hydrogen generation. The electrochemical gated semiconductor SI-SECM method proposed in this invention combines Schottky barrier with electrochemical titration, providing a robust and high-throughput platform for analyzing reactive species. It offers key mechanistic insights for understanding the structure-activity relationship of electrocatalytic materials and has broad application potential in various electrocatalytic systems. The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for fabricating an electrochemically gated high-throughput SI-SECM substrate based on a metal-semiconductor Schottky structure, characterized in that, Includes the following steps: S1 was made with FTO as substrate, and was subsequently ultrasonically cleaned with anhydrous ethanol, rinsed with acetone and cleaned with deionized water. It was then ultrasonically treated again in ethanol and dried under vacuum conditions. S2 is mixed with nano-TiO2 powder and water-soluble resin in a mass ratio of 7:3, and anhydrous ethanol is added and ultrasonically dispersed for 10 minutes to obtain a uniform TiO2 dispersion. S3 The TiO2 dispersion is sprayed onto the FTO conductive surface and then annealed to form a stable TiO2-FTO semiconductor layer; S4 attaches a metal mask template to the TiO2-FTO surface to seal off non-deposition areas; S5 uses a plasma magnetron sputtering instrument to sputter Pt onto the TiO2-FTO surface under a fixed vacuum and current. By employing a stepwise shielding sputtering method in the row and column directions, a two-dimensional Pt loading gradient is formed, resulting in a Pt-TiO2-FTO high-throughput array substrate containing multiple different Pt loadings.

2. According to the preparation method of claim 1, in step S1, the FTO size is 1.0 cm × 3.0 cm × 0.2 cm, the vacuum drying temperature is 80°C, and the drying time is 30 minutes.

3. According to the preparation method of claim 1, the TiO2 dispersion in step S2 is composed of 70.0 mg TiO2 powder, 30 mg water-soluble resin and 5 mL anhydrous ethanol.

4. According to the preparation method of claim 1, the nozzle diameter of the spray gun used in step S3 is 0.3 mm, the volume of TiO2 dispersion liquid drawn is 200 μL, the spraying area is 1.0 cm × 1.0 cm, and the annealing temperature is 400 °C.

5. According to the preparation method of claim 1, the metal mask in step S4 has a 9×9 open structure with a pore size of about 200 micrometers.

6. According to the preparation method of claim 1, in step S5, the sputtering chamber is filled with an argon atmosphere, the vacuum degree is 4.0 Pa, the sputtering current is 11 mA, and the time gradient is 0.5 min.

7. A high-throughput SI-SECM substrate based on a metal-semiconductor Schottky structure with electrochemical gate control, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.

8. A quantitative analytical method for in-situ titration of active hydrogen using electrochemically controlled high-throughput SI-SECM based on a metal-semiconductor Schottky structure, characterized in that... Includes the following steps: S6 Place the carbon microelectrode and the Pt-TiO2-FTO high-throughput array substrate prepared by any one of the preparation methods of claims 1-6 in an electrolyte containing FcMeOH, and adjust the distance between the tip and the array point to the position of complete collection efficiency; S7 applies a negative bias voltage to the array substrate, causing the TiO2 band to bend downwards and driving water molecules to be reduced on the Pt surface to generate active hydrogen. S8 removes the negative bias voltage, restoring the Schottky barrier at the Pt-TiO2 interface; After the negative bias is removed, S9 applies a potential to the tip for oxidizing FcMeOH, causing the generated FcMeOH to... + The transient titration current signal is obtained by reacting with the active hydrogen on the surface of the array points. S10 calculates the coverage of active hydrogen on the array point surface and its kinetic constants by integrating the titration current-time curve.

9. The analytical method according to claim 8, wherein the electrolyte for FcMeOH in steps S6-S10 consists of 0.1M KCl, 1mM FcMeOH, and 10mM KOH; the distance between the tip and the Pt array points is 2-3 micrometers; the potential applied to the substrate is 0V vs. RHE for 500 milliseconds; the potential used by the tip to oxidize FcMeOH is 1.3V vs. RHE; the titration current-time curve is collected for 50 seconds; and the delay time between substrate generation and tip collection is 1 millisecond, 200 milliseconds, 500 milliseconds, 1000 milliseconds, and 2000 milliseconds.

Citation Information

Patent Citations

  • Carbon nanotube array photocathode material and preparation method and application thereof

    CN102122579A

  • Photovoltaic devices with multiple junctions separated by a graded recombination layer

    CN103069604A